Proceedings of OceanObs'09: Sustained Ocean Observations and Information for Society 2010
DOI: 10.5270/oceanobs09.cwp.06
|View full text |Cite
|
Sign up to set email alerts
|

Biologging in the Global Ocean Observing System

Abstract: Miniature electronic data recorders and transmitters have revolutionized the way we study animals over the past decades, particularly marine animals at sea. But, very recently, animal-borne instruments have also been designed and implemented that provide in situ hydrographic data from parts of the oceans where little or no other data are currently available (even from beneath the ice in polar regions). Ocean data is delivered from animal-borne instruments via satellites in near real-time, which would enrich th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…In parallel, certain marine mammals have now been equipped with biogeochemical sensors allowing sustained data acquisition to be initiated in areas where data scarcity is generally the rule (e.g. Boehme et al, 2010). Biological oceanography is thus emerging from its data-limited foundations.…”
Section: An Under-sampled Ocean: Context and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, certain marine mammals have now been equipped with biogeochemical sensors allowing sustained data acquisition to be initiated in areas where data scarcity is generally the rule (e.g. Boehme et al, 2010). Biological oceanography is thus emerging from its data-limited foundations.…”
Section: An Under-sampled Ocean: Context and Challengesmentioning
confidence: 99%
“…Based on these technologies, pilot projects have been launched or are planed (Boehme et al, 2010;Claustre et al, 2010;Gruber, et al, 2010;Johnson et al, 2009, Testor et al, 2010. If, from these individual initiatives and biogeochemical pilot projects, we begin to think and implement in terms of networks, arrays and coordinated international efforts, we can expect a revolution in biogeochemical oceanography.…”
Section: An Under-sampled Ocean: Context and Challengesmentioning
confidence: 99%
“…We will also present briefly the first data collected using a new sensor that integrates fluorescence measurements into the basic CTD-SRDL tag. All details on the CTD-SRDL manufactured by the Sea Mammal Research Unit (SMRU) in Scotland are provided in the companion CWP by [1], along with a general discussion of the concept of using seals as oceanographic samplers. Physical data quality, calibration and validation procedures of the data collected by CTD-SRDL are presented in a companion "additional contribution" to OceanObs'09 [2].…”
Section: Charrassin J-bmentioning
confidence: 99%
“…4). Reference [17] studied a winter temperature and salinity time series collected by an elephant seal that foraged for several months close to Signy Island (60°43' S , 45°36' W), located at the northern limit of the seasonal sea-ice extension (see [1], this volume). Using local, one-dimensional ice production modelling and mixedlayer modelling, they showed that the evolution of upper layer salinity in this locality (as measured by the seal tag) is more likely to reflect sea-ice production rates occurring at higher latitude in the Weddell Sea, rather than the local freezing rates.…”
Section: Regional Oceanographic Studies In Ice-covered Areas: East Anmentioning
confidence: 99%
See 1 more Smart Citation